2008
DOI: 10.1038/onc.2008.54
|View full text |Cite
|
Sign up to set email alerts
|

NSC348884, a nucleophosmin inhibitor disrupts oligomer formation and induces apoptosis in human cancer cells

Abstract: Nucleophosmin (NPM), a multifunctional nucleolar phosphoprotein is dysregulated in human malignancies leading to anti-apoptosis and inhibition of differentiation.We evaluated the precise three-dimensional structure of NPM based on the highly conserved structure of Xenopus NO38 and its requirement to form dimers and pentamers via its N-terminal domain (residues, 1-107). We hypothesized that a small molecular inhibitor (SMI) that could disrupt the formation of dimers would inhibit aberrant NPM function(s) in can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 48 publications
6
93
0
Order By: Relevance
“…Similar to our findings, Qi et al (2008) have identified a small molecule, NSC348884, as an NPM inhibitor. Although NSC348884 possibly binds to the N terminus of NPM, which is different from where NPM aptamers bind to, it can disrupt NPM oligomerization and cause an upregulation of p53 as do NPM aptamers.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to our findings, Qi et al (2008) have identified a small molecule, NSC348884, as an NPM inhibitor. Although NSC348884 possibly binds to the N terminus of NPM, which is different from where NPM aptamers bind to, it can disrupt NPM oligomerization and cause an upregulation of p53 as do NPM aptamers.…”
Section: Discussionsupporting
confidence: 76%
“…This result validates the importance of NS and NPM in regulating rRNA biogenesis and controlling p53 pathway. Pharmacologic inhibition of NPM with NSC348884 (NPMi), previously reported to induce apoptosis in cancer cells (33), also significantly increases apoptosis in NRCMs (Fig. 3C), thus confirming a key role of NPM for cell survival.…”
Section: Ns and Npm Influence Cell Survival In Response To Apoptoticsupporting
confidence: 54%
“…Studies using a peptide derived from Rev protein, which binds nucleophosmin, suppressed tumor growth through apoptosis by upregulating the transcriptional activity of p53. Recently, NSC348884, a pharmacophore that targets nucleophosmin, has been shown to inhibit the proliferation of various cancer cell lines through the induction of apoptosis (35). Likewise, it has been shown that C in the presence of 0.02% sodium azide and then fixed with methanol.…”
Section: Discussionmentioning
confidence: 99%
“…This stretch of basic residues interacts with the N-terminal globular domain of nucleophosmin, which has been shown to be involved in nucleophosmin pentamer formation and chaperone activity. It is noteworthy that molecules that interact with the N-terminal domain of nucleophosmin, such as the Rev peptide (37) or the small molecule NSC 348884 (35), disrupt nucleophosmin oligomer formation and induce apoptosis. From this set of results, we can hypothesize that N6L, which is a pseudopeptide rich in Lys and Arg residues and displays high affinity for nucleophosmin, disrupts its oligomerization and/or the formation of complexes between nucleolin, nucleophosmin, and oncoproteins.…”
Section: Discussionmentioning
confidence: 99%